AN OVERVIEW OF THE TECHNIQUE FOR SEISMICITY MICROZONATION MAPPING OF THE ULAN‐UDE CITY TERRITORY - Vasilii I. Dzhurik; Tsyren A. Tubanov; Sergei P. Serebrennikov; Alexander F. Drennov; Evgenii V. Bryzhak; Alexander Yu. Eskin (Геодинамика и тектонофизика, 2015)
For purposes of seismicity microzonation of the Ulan‐Ude city territory, engineering geophysical studies are conducted to reveal which types of rocks and soils are dominant in the study area and to classify them by site‐specific velocities of P‐ and S‐waves and amplitude‐frequency characteristics. The article describes a technique for establishing the baseline seismic signal corresponding to parameters of relatively strong earthquakes in potential earthquake foci (PEF) zones. It is shown that the established baseline signal is applicable. Presented are results of theoretical calculations based on seismicity‐soil models providing reference parameters of bedrock, medium and water‐saturated soils (soil categories 1, 2 and 3, respectively).Seismic impacts are assessed for the zone with the baseline seismic intensity of 8 points, as per MSK‐64 seismic intensity scale. The reference model is used to identify zones with seismic intensity from 7 to 9 points in the city territory, and it is established that such zones differ in thickness of water‐saturated and non‐water‐saturated soil layers. As a result, a schematic map showing the main parameters of seismic impacts is constructed in the first approximation. The obtained data are useful for the development of recommendations concerning further engineering seismological studies and activities for the appropriate revision and upgrading of the seismic microzonation technique in order to complete seismic microzonation of the Ulan‐Ude city territory.